Multidisciplinary Treatment of Head and Neck Cancer - Varkey, Prashanth (Thieme Medical Publishers, 2010)
Head and neck cancer remains a significant cause of morbidity worldwide. Multimodality treatment is often the only way to achieve improved function, quality of life, and survival, calling for a multidisciplinary team approach, particularly in view of the rapid advances being made in various fields. The roles of the head and neck surgeon and reconstructive surgeon are discussed, together with the input afforded by specialists in areas such as diagnostic imaging, radiation therapy, medical oncology, and gene therapy. Telemedicine is of importance in centers where multidisciplinary expertise is not available.